2020
DOI: 10.3389/fonc.2020.00305
|View full text |Cite
|
Sign up to set email alerts
|

CaSR Induces Osteoclast Differentiation and Promotes Bone Metastasis in Lung Adenocarcinoma

Abstract: Objective: Explore the mechanism of CaSR's involvement in bone metastasis in lung adenocarcinoma. Methods: Immunohistochemistry (IHC) was used to detect the expression of calcium-sensing receptor (CaSR) in 120 cases of lung adenocarcinoma with bone metastasis. Stably transfected cell lines with CaSR overexpression and knockdown based on A549 cells were constructed. The expression of CaSR was verified by western blot and qPCR. The proliferation and migration abilities of A549 cells were tested using cholecystok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Its expression is low or absent in normal lung tissue, whereas it is significantly higher in lung cancer tissue (173). Moreover, Lian et al (174) demonstrated that the expression of CASR in 120 cancer tissues with bone metastasis was significantly higher than that recorded in non-metastatic lung cancer tissues. Another study found that the increase of CASR was the result of PTHrP and NF-kB upregulation, which was also positively correlated with bone metastasis in lung cancer (173,175,176).…”
Section: Calcium Sensing Receptor (Casr)mentioning
confidence: 99%
“…Its expression is low or absent in normal lung tissue, whereas it is significantly higher in lung cancer tissue (173). Moreover, Lian et al (174) demonstrated that the expression of CASR in 120 cancer tissues with bone metastasis was significantly higher than that recorded in non-metastatic lung cancer tissues. Another study found that the increase of CASR was the result of PTHrP and NF-kB upregulation, which was also positively correlated with bone metastasis in lung cancer (173,175,176).…”
Section: Calcium Sensing Receptor (Casr)mentioning
confidence: 99%
“…(73). In addition to growth factors, tumor cells respond to calcium ions (via CaSR) released in the process of bone resorption (74).…”
Section: Tumor Cell Migration Adhesion and Invasionmentioning
confidence: 99%
“…It stimulates osteoclasts directly and indirectly via osteoblasts ( 73 ). In addition to growth factors, tumor cells respond to calcium ions (via CaSR) released in the process of bone resorption ( 74 ).…”
Section: Osteolytic Bone Diseasementioning
confidence: 99%
“…In the context of bone diseases, OCs are thought to be involved in several bone disorders, such as osteoporosis, Paget's disease, rheumatoid arthritis, and especially cancer metastasis [12]. Over few decades, there have been lots of considerable efforts on elucidation of the regulatory roles of OCs in metastatic diseases that originate from multiple myeloma, prostate cancer, breast cancer, and/or lung cancer [13,14]. In fact, many animal and clinical researches have indicated that OCs play a central role in strengthening the occurrence and progression of bone metastasis through a mechanism underlying the release of factors such as interleukin (IL)-1 and transforming growth factor-beta (TGF-β) that stimulate proliferation, differentiation and growth of metastatic cancer cells.…”
Section: Oc-mediated Regulation Of Bone Metastasismentioning
confidence: 99%